PEMBERANTASAN KORUPSI DALAM PENGADAAN BARANG DAN JASA MELALUI INSTRUMEN HUKUM PIDANA DAN ADMINISTRASI - Amiruddin Amiruddin (Jurnal Media Hukum, 2012)
Corruption in the procurement of goods and services cannot be eradicated only by a single criminal law instrument. The punishment theory, which aims at making the corruptors or people who want to do corruption scared and prevent the from corruption, is not effective enough to eradicate corruption, since the corruptors are mostly officers and the modus operandi (method of operation) is very dynamic. Therefore, corruptions are difficult to be detected. Thus besides employing criminal law as an instrument to eradicate corruption in the procurement of goods and services, administrative law instrument, which focuses on the control and administrative sanction, is also needed. Officers who are proven doing violation can be punished with the dismissal sanction, while the dishonest providers of goods and services can be punished by putting them in a black list or terminating their business permits. In conlusion, by combining use of criminal law and administrative law, the eradication of corruption in the procurement of goods and services becomes more effective.